An in vivo study on the therapeutic effect of sampaguita leaves on induced oral ulcers in guinea pigs - Fernandez, Caroline R.; Viray, Ellen Agnes; Estaniel, Cynthia (Adviser).
This paper aims to study the therapeutic effect of Jasminum Sambac otherwise known as sampaguita on traumatic oral ulcers in guinea pigs. In this experiment, the electrosurgical unit was used to induce oral ulcers in the lower mucosa of nine guinea pigs. Three of these guinea pigs had their oral ulcers treated with sampaguita extract; the other three guinea pigs were treated with Pyralvex solution while the rest of the guinea pigs did not receive any treatment. Clinically, it was found that healing of oral ulcers in both Pyralvex and sampaguita treated guinea pigs occured earlier than the ulcers of the guinea pigs which were left untreated. Microscopically, the healing process in both Pyralvex and sampaguita treated guinea pigs did not have much difference. The ulcers of the untreated guinea pigs however, showed delayed healing.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Sampaguita leaves -- Therapeutic use; Medicinal plants; Herbs -- Therapeutic use; Botany, Medical -- Therapeutic use